An Exploration of Frequent Service Failures in the Brazilian Airline Industry. Issue 1 (2nd January 2017) - Lorenz, Melanie P.; Johnson, Catherine M.; Barakat, Livia L.
ABSTRACT: This study explores how customer evaluations of service failures and failure recurrence impact negative emotions and intent to complain. A survey of 589 Brazilian airline passengers demonstrates the meditational effect of negative emotions such that customers who perceive failures as severe and/or preventable by the airline develop more negative emotions, which subsequently increases intent to complain. We also demonstrate the moderating role of failure recurrence such that failure recurrence reduces the effect of failure severity on negative emotions. Our findings have important implications for managers and airlines in order to mitigate negative outcomes following a service failure.